2019
DOI: 10.1001/jama.2019.16275
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab and the Challenges for Biosimilars

Abstract: Biologic drugs are expensive therapeutic agents and represent a large and growing segment of pharmaceutical spending. In particular, at nearly $20 billion in sales in 2018, adalimumab (Humira) dominates the worldwide biologic market, with more than twice the annual sales of the second-highest selling drug, lenalidomide (Revlimid). 1 Biosimilars have long been viewed as a solution to the high price of injectable biologic drugs like adalimumab. There are now 23 approved biosimilars in the United States with hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…To date, these have focused mostly on infliximab, as the first infliximab biosimilars were approved in 2013, 85 whereas adalimumab biosimilars have only been available since late 2018 in Europe, and are not yet available in the United States owing to patent issues. 90 A meta-analysis of 11 observational studies conducted with an infliximab biosimilar demonstrated excellent efficacy and safety across both CD and ulcerative colitis patients. 91 More recently, a large national observational study was conducted in over 3000 infliximab-naïve patients with ulcerative colitis in France.…”
Section: Introductionmentioning
confidence: 99%
“…To date, these have focused mostly on infliximab, as the first infliximab biosimilars were approved in 2013, 85 whereas adalimumab biosimilars have only been available since late 2018 in Europe, and are not yet available in the United States owing to patent issues. 90 A meta-analysis of 11 observational studies conducted with an infliximab biosimilar demonstrated excellent efficacy and safety across both CD and ulcerative colitis patients. 91 More recently, a large national observational study was conducted in over 3000 infliximab-naïve patients with ulcerative colitis in France.…”
Section: Introductionmentioning
confidence: 99%
“…1 Because of their high and rising prices and their widespread use, these agents represent a large and growing segment of pharmaceutical spending in the United States. 2 Increases in list prices of TNF inhibitors are worrisome because they can hinder patient affordability and access to these essential medications, particularly in uninsured and underinsured populations. 3 There are 4 self-administered injectable TNF inhibitors available in the U.S. market-all brand drugs.…”
Section: What This Study Addsmentioning
confidence: 99%
“…However, the window for these biosimilars to have an impact on healthcare costs is narrowing owing to delays in market introduction and utilization. Advanced, more expensive treatments are taking the place of current biologics, lessening the financial impact of current biosimilars [ 30 ]. For biosimilars to cause significant flattening of the cost-expenditure curve, strong acknowledgment of their efficacy is needed by oncologists and their patients globally.…”
Section: Reviewmentioning
confidence: 99%